The new japanese painting and sculpture - Lieberman, William S.; San Francisco Museum of Art, San Francisco; Denver Art Museum, Denver; Krannert Art Museum, University of Illinois, Urbana; Joslyn Art Museum, Omaha; The Columbus Gallery of fine Arts, Columbus; The Museum of Modern Art, New York; Baltimore Museum of Art, Baltimore; Milwaukee Art Center, Milwaukee (New York : The museum of Modern Art, 1966)
Abe, Nobuya ; Akana, Hiroshi ; Arakawa, Shusaku ; Azuma, Kengiro ; Domoto, Hisao ; Eguchi, Shyu ; Hiraga, Key ; Inokuma, Genichiro ; Isobe, Yukihisa ; Izumi, Shigeru ; Kawabata, Minoru ; Kawashima, Takeshi ; Kikuhata, Mokuma ; Kimura, Reiji ; Skojima, Nobuaki ; Kuno, Shin ; Kusumoto, Masaaki ; Miki, Tomio ; Mogami, Hisayuki ; Motonaga, Sadamasa ; Mukai, Ryokichi ; Mukai, Shuji ; Nagare, Masayuki ; etc.
The new japanese painting and sculpture, San Francisco Museum of Art, San Franciso, California, April 29 - June 13; 1965 ; Denver Art Museum, Denver, Colorado, October 2 - November 14, 1965 ; Krannert Art Museum, University of Illinois, Urbana, Illinois, December 12, 1965 - January 30, 1966 ; Joslyn Art Museum, Omaha, Nebraska, February 26 - March 20, 1966 ; The Columbus Gallery of Fine Arts, Columbus, Ohio, April 7 - May 6, 1966 ; The Museum of Modern Art, New York, October 17 - December 26, 1966 ; Baltimore Museum of Art, Baltimore, Maryland, January 24 - March 19, 1967 ; Milwaukee Art Center, Milwaukee, Wisconsin, April 13 - May 14, 1967
boek
Keywords: Japan